MAKNA DAN SIMBOL GERAK TARI RADDAT KOKO DI DESA SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Hastuti, Liza; Istiandini, Winda; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research background is to know about txhe meaning and symbol of dance movement Raddat Koko. The purpose of this research are 1) to describe the symbol in dance movement Raddat Koko in Sekuduk Village Sejangkung District Sambas Regency, 2) to describe the meaning in dance movement Raddat Koko in Sekudduk Village SejangkungSubdistrict Sambas District, 3) to describe the implementation of symbols and meaning of dance movement Raddat Koko in grade X SMA Negeri 1 Selakau on the subjects of Art Culture. The motion is, among others, the hormat motion, ancang-ancang 1, ancang-ancang 2, ancang-ancang 3, the menyerang motion 1 and menyerang 2. Motivation presents a symbol of respect that has meaning of homage to the audience who has been present. Ancang-ancang 1 presents a stalking symbol that has the meaning of stalking the place where the Dutch weapons hide. Ancang-ancang 2 presents a ready-to-play symbol that has the meaning of making a square off to move to a Dutch-owned hideout. Ancang-ancang 3 presents a preparatory symbol for an attack that has the meaning of performing the planned motion against the enemy. Menyerang 1 presents a symbol ready to fight against an opponent who has a ready-to-war meaning. Menyerang 2 represents the already attacking symbol has the meaning of war with unyielding. Keywords: meaning, symbol, motion, Raddat Koko traditional dance.